Evaluación de la eficiencia de bioadsorción de cáscara de banana (musa x paradisiaca) para la remoción de plomo en aguas residuales de la lubricadora “Lubriautos Mafriss” - López Bravo, Héctor David (2020)
This research topic was aimed at evaluating the efficiency of banana peel (Musa x paradisiaca), for the removal of lead in wastewater from the "LUBRIAUTOS MAFRISS" lubricator. To carry out the research, the banana peel was used as the main material, which went through a dehydration process in a stove at a constant temperature of 45° C for 5 days, after grinding and sieving until obtaining a powder as a final result of uniform grain size banana was separated into three different concentrations of 20g, 30g and 40g. The applied experimental scheme was a completely randomized design with 3 treatments and 4 repetitions, obtaining a total of 12 experimental units to which the banana dust concentrations already described were applied, carrying out a bioadsorption process of lead in 1 liter of residual water. After 48 hours of contact between the powder and the residual water, the lead analysis was carried out for each experimental unit. The removal percentages resulting from the evaluated parameter were processed in Microsoft Excel and InfoStat 2016 Software. As a result, it was evidenced that the untreated water had a concentration of 0.73 mg / l of lead, while once the respective treatments of 20, 30 and 40g all favorably decreased their concentration to a negligible <0.01 mg / l, thus fulfilling the hypothesis of a high adsorption effectiveness of banana powder. As for the economic viability, the cost of the treatment turned out to be $ 10.74, which is feasible given its high efficiency.